Preparation of Functional Pasta Supplemented with Amaranth Pregelatinized Extruded Flour - Bello-Pérez, Luis A.; Cabello-Vazquez, Jesus A.; Carmona-Garcia, Roselis-; Patiño-Rodriguez, Omar; Alvarez-Ramirez, Jose (Frontiers in Food Science and Technology, 2022)
Semolina pasta with improved nutritional properties is increasingly demanded by consumers. High protein content and low starch digestibility are features desired for a functional pasta. In this work, amaranth flour was used for 50% supplementation of semolina in pasta preparation. Raw amaranth flour increased protein from 11.7 g/100 g to about 14.0 g/100, dietary fiber from 6.8 g/100 g to about 8.0–10.0 g/100 g. However, raw amaranth flour deteriorated the texture of cooked pasta by increasing hardness from 15.7 to 52.8 N and reducing cohesiveness from 0.71 to 0.55. Pregelatinizations at 50 and 100% were explored to reduce the adverse effects of raw amaranth flour. The gelatinized amaranth flour mimicked the texture of semolina pasta, although cooking loss increased from 3.3 g/100 g to about 9.2 g/100 g, and the water absorption showed a marked reduction from 116.4% to about 80.0–84.0%. The in vitro starch digestibility was similar for pasta made with semolina and pasta containing pregelatinized starch, although digestibility decreased from 95 to 85% for raw amaranth flour. Overall, the results showed that amaranth flour offered advantages and drawbacks for the formulation of pasta with improved nutritional features.